2021
DOI: 10.1007/s10792-021-02003-9
|View full text |Cite
|
Sign up to set email alerts
|

Wave front aberrations induced from biomechanical effects after customized myopic laser refractive surgery in finite element model

Abstract: A customized myopic refractive surgery was simulated by establishing a finite element model of the human eye,after which we studied the wavefront aberrations induced by biomechanical effects and ablation profile after wavefrontguided LASIK surgery.Methods: Thirty myopia patients (i.e., 60 eyes) without other eye diseases were selected. Their ages, preoperative spherical equivalent, astigmatism, and wavefront aberration were then obtained, in addition to the mean spherical equivalent error range -4 to -8D. Afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, the influence of corneal biomechanics and wound healing on spherical aberration cannot be ignored. HOAs are associated with biomechanical weakness of the cornea (Du et al, 2022; Fang et al, 2020). SMILE retains better mechanical properties than LASIK, which also explains the smaller spherical aberration introduced after SMILE (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of corneal biomechanics and wound healing on spherical aberration cannot be ignored. HOAs are associated with biomechanical weakness of the cornea (Du et al, 2022; Fang et al, 2020). SMILE retains better mechanical properties than LASIK, which also explains the smaller spherical aberration introduced after SMILE (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researches has shown that increased coma is associated with corneal flap creation and small intraoperative eye movements [17,18]. Du, et al, reported that coma was the main aberration caused by corneal biomechanical changes [19]. One of the limitations of our study is the small sample that was studied.…”
Section: Discussionmentioning
confidence: 81%